An Expert System for Selecting an Appropriate Solid Waste Treatment Technology - Abu Samah, Mohd Armi (2009)
The industrialisation, urban development and increasing population have brought about waste disposal problem that pose a tremendous challenge to the planners and managers of Malaysia. Therefore the advent of industrialisation, new environmental problems have also emerged, in the form of toxic and hazardous waste, demanding immediate attention and containment measures. Thus, it is not surprising that a primary concern in Malaysia is the management and disposal of an increasing amount of waste which contribute to environmental degradation in the all area especially in urban area. Solid Waste Treatment Technology (SWATT) expert system is a computer program for decision making in solid waste management. Solid Waste Treatment Technology (SWATT) expert system using application of Analytical Hierarchy Process (AHP) usually can be ranked according to solid waste management hierarchy as described in “EPA’s Agenda” for Action. Following the integrated approach in solid waste management, Analytical Hierarchy Process (AHP) is being applied using a multi-level hierarchical structure of objectives, criteria, subcriteria, and alternatives. Based on knowledge acquisition from multiple sources, two forms of hierarchy structure has been developed and it was divided into two sections namely general hierarchy structure and specific hierarchy structure for selection of technologies; [1] for selection of general technology where political support, technical expertise, environmental impact, market potential, community involvement and technology cost become as a criteria while alternative consist of three distinct technologies (recycling, composting and incineration) and four combinations of the respective technologies [2] for selection of specific technology in more detail. Inputs data from the experts are used for the pairwise comparison matrix. Through the matrix of pairwise comparison, solid waste treatment technology will be ranked according to their height value of benefit technology. Based on consistency ratios a value of 10 percent or less will be accepted; otherwise the process must be re-evaluated. These comparisons will be used to obtain the weight of importance of the decision criteria, and the relative performance measures of the alternatives in terms of each individual decision criterion. If the comparisons are not perfectly consistent, then the AHP technique will provides a mechanism for improving consistency. To verify, the effectiveness of SWATT expert system has been evaluated for two case study; Kajang Municipal Council and Sepang Municipal Council. Through consultation session, expert system suggested that the best selection of technology is combination of recycling and incineration technology of which the weight is 0.17 for Kajang while combination of recycling and composting technology of which the weight is 0.13 for Sepang. The effectiveness of SWATT expert system was evaluated by selected experts and system engineer that demonstrated satisfactory results as well as user will be able to have the benefits of informed decision making.